PENGARUH BELANJA INFRASTRUKTUR PEMERINTAH TERHADAP KAPITALISASI PASAR KELOMPOK INDUSTRI INFRASTRUKTUR, UTILITAS DAN TRANSPORTASI PADA PERUSAHAAN YANG TERDAFTAR DALAM BURSA EFEK INDONESIA (STUDI DATA TIME SERIES 2005-2014) - Deni Istiono Istiono (Program Studi Manajemen, Universitas Al Ghifari, 2020)
This research aims to determine the effect of government infrastructure expenditure to market capitalization infrastructure, utilities and transportation industry of listed companies in the Indonesian Stock Exchange (IDX) during 2005-2014. Research analysis using descriptive and verification. Data used is time series data as realization of direct expenditures of government in infrastructure sector which consists of transportation and communication. Market capitalization data is capitalization of industry group infrastructure, utility and transportation companies listed on the Indonesian Stock Exchange (IDX) during 2005-2014. Analysis data used descriptive and verification. Descriptive analysis is used to describe the research variables development. The verification analysis used to examine the effect between variables with include the selection models test, specifications model test, normality test, regression test, coefficient determination test, statistical t and f test. The result analysis showed government infrastructure expenditure variables is positive and significant impact on the market capitalization of the infrastructure, utilities and transportation industry listed companies in the Indonesian Stock Exchange during 2005-2014, with the determination level of 47.47% and the remaining 53.52% is explained by other variables that are not described or include in the research models function such as National income, inflation, exchange rates and others. Therefore central government should be consistent on each target and development activities that have been assigned in infrastructure expenditure every year. It is important to do, so the financing gap does not encourage inflation that couse high cost in the production process due to the inflation of infrastructure commodity. In addition, effective control efforts to development process is being carried out and also continue by synergy among the stakeholders that being implementation process development is done on time, as well as efforts to establish strategic policies and legal certainty for investors. So the investment climate more conducive to attracting private investors invest in the infrastructure, utilities and transportation sector in the Indonesian Stock Exchange. Key words : MARKET CAPITALIZATION, INFRASTRUCTURE, UTILITIES AND TRANSPORTATION INDUSTRY, GOVERNMENT INFRASTRUCTURE EXPENDITURE, INDONESIAN STOCK EXCHANGE.